Kajian Kajian Historis Novel Perawan Remaja Dalam Cengkeraman Militer Karya Pramoedya Ananta Toer - Anita, Anita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
The problems examined in this study are: 1) how is the history of Indonesian women's lives in the Novel Virgin Adolescents in the Grip of the Military? The purpose of this research is to find out the lives of Indonesian women in the novel of the virgin teenager in the military grip. historical research methods (Historical Methods). The steps in historical method research include: heuristics, verification (source criticism), interpretation and historiography. The source of the data used is the Novel Adolescent Virgins in the Cengkaran of the Military: Records of the island of Buru by Pramoedya Ananta Toer. The results showed that Japanese propaganda in the promise to educate the Indonesian generation so that they could devote themselves to independence, the promise to send Indonesian teenage virgins to Tokyo and Shonanto which was never officially announced, especially not listed in the Osamu Serei (State Gazette), resulted in many parents giving up girls to leave their hometowns and families to take dangerous voyages, some even not of their own volition but because of their parents' fear of the Japanese threat. Selecting young virgins to fulfill the sex dreams of Japanese soldiers, some even dying in agony, never got the chance to learn as promised. The suffering they experienced was varied and really shook the feelings of humanity. Not a few teenage virgins who become exiles in the interior of the island of Buru and find it difficult to return to old age.